2006
DOI: 10.2807/esw.11.18.02952-en
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of low pathogenicity H7N3 avian influenza in UK, including associated case of human conjunctivitis

Abstract: On 26 April 2006, the veterinary authorities in the United Kingdom reported that there had been an outbreak of avian influenza type A/H7 among a 35 000-bird housed poultry flock in eastern England, United Kingdom.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
57
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 0 publications
0
57
0
1
Order By: Relevance
“…Cases of human infection by H7 influenza viruses have been reported sporadically since 1979 (51), caused by both low-and high-pathogenicity avian influenza (LPAI and HPAI, respectively) H7 viruses of the Eurasian and North American lineages. Outbreaks associated with human infections were reported in 2002 and 2003 in the United States (7,8), 2004 in Canada (7,23,49), in 1995 and 2006-2007 in the United Kingdom (1,15,27,33), in 2002 in Italy (37), and in 2003 in the Netherlands (17,25). The 2003 outbreak in the Netherlands was caused by an HPAI H7N7 subtype and was the source of infection for 89 people exposed to affected poultry, including three cases of possible human-to-human virus transmission (17).…”
mentioning
confidence: 99%
“…Cases of human infection by H7 influenza viruses have been reported sporadically since 1979 (51), caused by both low-and high-pathogenicity avian influenza (LPAI and HPAI, respectively) H7 viruses of the Eurasian and North American lineages. Outbreaks associated with human infections were reported in 2002 and 2003 in the United States (7,8), 2004 in Canada (7,23,49), in 1995 and 2006-2007 in the United Kingdom (1,15,27,33), in 2002 in Italy (37), and in 2003 in the Netherlands (17,25). The 2003 outbreak in the Netherlands was caused by an HPAI H7N7 subtype and was the source of infection for 89 people exposed to affected poultry, including three cases of possible human-to-human virus transmission (17).…”
mentioning
confidence: 99%
“…30 A 2007 LPAI H7N3 outbreak in poultry in the United Kingdom resulted in conjunctivitis in an infected poultry worker. 31 A study of U.S. veterinarians who worked with birds reported they had significantly higher H5, H6, and H7 antibody levels than a control group. 32 These studies demonstrate the importance of protecting poultry workers when an AI outbreak in poultry is suspected or confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 However, several studies indicate that workers have been infected during AI outbreaks in poultry. [27][28][29][30][31][32][33] A serological evaluation of workers exposed during the HPAI H5N1 outbreak in Hong Kong in 1997 found that approximately 3% of government workers involved in the poultry culling operation and 10% of poultry workers were seropositive. 28 During a 2003 outbreak of HPAI H7N7 in the Netherlands, infection was confirmed in 89 people, with conjunctivitis being the predominant symptom reported.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, other sporadic cases of H7N3 LPAI and HPAI virus infections occurred in Canada (2004), resulting in two cases of conjunctivitis and mild respiratory symptoms. In Wales in 2007, an infection with H7N2 LPAI virus was associated with poultry obtained from a live bird market (Nguyen- Van-Tam et al 2006, Editorial team 2007. The patients had symptoms of conjunctivitis, flu-like symptoms, and neurological and gastrointestinal symptoms (Capua & Alexander 2004, Editorial team 2007.…”
Section: H7 In Humansmentioning
confidence: 99%